A Systematic Review of Stem Cell Applications in Maxillofacial Regeneration - Man Hung; Mahsa Sadri; Melanie Katz; Connor Schwartz; Amir Mohajeri (MDPI AG, 2024)
Introduction: Regenerative medicine is revolutionizing oral and maxillofacial surgeries with stem cells, particularly mesenchymal stem cells, for tissue and bone regeneration. Despite promising in-vitro results, human trials are limited. A systematic review is needed to evaluate stem cell efficacy in maxillofacial issues, aiming to improve surgical outcomes and patient satisfaction. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guidelines, this review included peer-reviewed articles (2013-2023) on stem cells in oral surgery, excluding non-English publications, abstracts, reviews, and opinion pieces. Searches were conducted in PubMed, Web of Science, OVID, Cochrane, Dentistry & Oral Sciences Source-Ebscohost, and Scopus. Two authors independently screened titles and abstracts, resolving disagreements by consensus. Full-text analysis involved extracting key data, verified by a secondary reviewer and additional quality checks. Results: From 3540 initial articles, 2528 were screened after removing duplicates, and 7 met the inclusion criteria after excluding irrelevant studies. Key themes included the safety and efficacy of stem cell therapy, and bone regeneration and quality. Studies predominantly used mesenchymal stem cells. Findings showed positive outcomes in clinical safety and effectiveness and significant potential for bone regeneration. Conclusions: This systematic review highlights the potential of stem cell therapies in maxillofacial applications, supporting their safety, efficacy, and bone regeneration capabilities. Further research is needed to standardize protocols and confirm long-term benefits.